Pembuatan Perkebunan dengan Air Pegunungan untuk Meningkatkan Penghasilan di Desa Batu Keramat Kecamatan Kota Agung Timur - Ordas Dewanto; Bambang Irawan; Rahmat Catur Wibowo (Jurnal Abdimas Multidisiplin, 2022)
Purpose: water utilization is used to increase or create new types of business in the plantation sector. There are 2 groups of farmers and livestock that serve as partners, namely Eko Makmur Sejahtera and Yamin Batu Keramat. Both partners already have farming businesses such as rice, vegetables, and fruits. The two partners' farms are already available with sufficient yields. Method: The Participatory Rural Approisal method which involves the farmer community in the overall activity. The implementation of this method is through provide counseling, training, and giving demonstrations as well as evaluation to see the effectiveness of the program, so that the program will be socialized properly and efficiently. Result: The Unila Service Team offered a solution to increase farmers community monthly income, so plantations were made. The Unila Service Team provides insight and knowledge on how to optimize the manufacture of plant stands, water reservoirs, and design of waterways to the households; Provide training on business management, marketing systems and management, as well as financial management, especially those related to plantation business; provide knowledge and insight to target audiences, especially farmer community, by providing training and practice on determining groundwater depth for well construction. Limitation: Initial and final evaluation of the service area; Counseling to the community; Implementation of the design of water use from the highlands to the partner site; and make plantations with the aim of increasing business.